The cost efficiency improvement of Norwegian banks can be explained by automation and digitalisation - Henrik Andersen (Norges Bank, 2020)
Operating costs in the Norwegian banking sector have been reduced considerably in recent decades, both as a share of income and assets. This has increased banks' resilience to increased losses and reduced the risk of crises. In this article, I analyse how costs have been reduced and the main drivers of the cost efficiency improvement. The results suggest that automation and the digitalisation of banks' operations have played a key role in improving cost efficiency.
hdl:11250/2690371
Keywords: 330; banks; costs; digitalisation; regulation; business cycle